(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Classical sources place Hispano-celtic population in both Southwestern and Galician regions, apart from Celtiberia; the epigraphic distribution of the nomina gentilicia formed with the -icus suffix (that is to Celtics’ liking) agrees with these areas.